2020
DOI: 10.7759/cureus.11770
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 Fluorodeoxyglucose PET/CT Images of Hidradenitis Suppurativa Mimicking Metastasis in a Patient With Small Cell Lung Carcinoma

Abstract: A 54-year-old male patient with metastatic small cell lung carcinoma received chemotherapy and in followup he was referred to positron emission tomography (PET)/CT scan for re-staging. In addition to the primary disease, increased Fluorine-18 fluorodeoxyglucose (F-18 FDG) uptake was detected in skin and subcutaneous fat tissue in the axillary, periscrotal, and perianal regions, which was later proven as hidradenitis suppurativa in PET/CT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Similarly, in a case report of a 54-year-old man with metastatic small-cell lung cancer and a history of HS, FDG-PET scans revealed an increased uptake in the axillary, periscrotal, and perianal regions, which were clinically confirmed to be HS. Subsequent histopathological evaluation via biopsy confirmed the HS diagnosis [33]. FDG-PET/CT accurately detected both subclinical and clinical sites of HS involvement.…”
Section: Case Reportsmentioning
confidence: 68%
See 4 more Smart Citations
“…Similarly, in a case report of a 54-year-old man with metastatic small-cell lung cancer and a history of HS, FDG-PET scans revealed an increased uptake in the axillary, periscrotal, and perianal regions, which were clinically confirmed to be HS. Subsequent histopathological evaluation via biopsy confirmed the HS diagnosis [33]. FDG-PET/CT accurately detected both subclinical and clinical sites of HS involvement.…”
Section: Case Reportsmentioning
confidence: 68%
“…Five articles featured case reports on the incidental detection of HS using FDG-PET scans while investigating malignant metastases. These case reports emphasized the capacity of FDG-PET scans to detect HS and demonstrated that detected lesions require further evaluation through biopsy to exclude occult malignancy [24,[33][34][35][36]. The last two articles comprised comprehensive reviews on the usefulness of various radiological techniques in diagnosing and managing HS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations